2020
DOI: 10.1016/j.eururo.2019.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Improved Prostate Cancer Biopsy Grading by Incorporation of Invasive Cribriform and Intraductal Carcinoma in the 2014 Grade Groups

Abstract: E U R O P E A N U R O L O G Y 7 7 ( 2 0 2 0 ) 1 9 1 -1 9 8 a v a i l a b l e a t w w w . s c i e n c e d i r e c t . c o m j o u r n a l h o m e p a g e : w w w . e u r o p e a n u r o l o g y . c o m Abstract Background: Grade groups (GGs) are an important parameter for therapeutic decision making in prostate cancer (Pca) patients. Invasive cribriform and/or intraductal carcinoma (CR/IDC) has an independent prognostic value for disease outcome, but are not included in the GG limiting their clinical use. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 29 publications
4
63
0
Order By: Relevance
“…Furthermore, recent studies have indicated that biopsies have a moderate sensitivity of 43–47% for detecting cribriform architecture 21,22 . Despite moderate concordance of growth patterns between biopsy and radical prostatectomy specimens, incorporation of cribriform architecture into the Grade Groups has better discriminative value for disease‐specific survival and metastasis‐free survival 20 . In biopsies, we previously demonstrated that subtraction of one point of the Grade Group if no cribriform architecture was present was a simple and valuable modification of the current prostate cancer grading scheme.20…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, recent studies have indicated that biopsies have a moderate sensitivity of 43–47% for detecting cribriform architecture 21,22 . Despite moderate concordance of growth patterns between biopsy and radical prostatectomy specimens, incorporation of cribriform architecture into the Grade Groups has better discriminative value for disease‐specific survival and metastasis‐free survival 20 . In biopsies, we previously demonstrated that subtraction of one point of the Grade Group if no cribriform architecture was present was a simple and valuable modification of the current prostate cancer grading scheme.20…”
Section: Discussionmentioning
confidence: 93%
“…In previous sextant biopsy studies with long‐term follow‐up, biopsy GG2− patients had similar biochemical recurrence‐free and disease‐specific survival as GG1 patients 16,17 . Therefore, it has been proposed that patients without cribriform architecture might be eligible for active surveillance 15–20 . However, prostate biopsies are subject to significant sampling errors with tumour undergrading in up to 40%, and there is low sensitivity for detection of cribriform architecture 21–23 .…”
Section: Introductionmentioning
confidence: 99%
“…Van Leenders et al recently proposed an alternative method of incorporating IDCP into the current GrG scheme by modifying the grade on the basis of the presence of any amount of IDCP and/or cribriform carcinoma. 16 In a large series of RP specimens, Kato et al found that incorporating the presence of IDCP, regardless of extent or morphological type, into the GrG system was predictive of biochemical recurrence. 17 Both of these studies propose integrating the presence of any amount of IDCP into the grading system to improve prognostication.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has defined cribriform architecture as an epithelial sheet (a) in which the majority of tumour cells do not contact the surrounding stroma, (b) with a gland-like space surrounding less than half of the sheet circumference, and (c) with regular intercellular lumens clearly visible on haematoxylin and eosin (H&E)stained sections (Figure 2). 55,56 The first criterion (a) distinguishes a cribriform pattern from complex fused glands in which most if not all tumour cells are still in direct contact with subtle connective tissue cores present within the lesion. The second criterion (b) arbitrarily distinguishes a cribriform from a large glomeruloid pattern in which gland-like spaces surround more than half of the central protrusion.…”
Section: Invasive Cribriform Growth Pattern Delineationmentioning
confidence: 99%